Perancangan Logo Branding Tropickled Asinan Buah - Bunga Serina (Jurnal Indonesia Sosial Teknologi, 2022)
Homemade pickled fruit which is one of the medium-sized businesses in the field, especially food, over time many similar businesses develop which make competition tougher, the solution to create a characteristic and identity Homemade pickled fruit requires a logo or identity so that it can compete with similar businesses. The main objective of this study project is to create a corporate identity that includes a logo and placement on each merchandise, with an identity design that will be applied to various supporting media to enhance the positive image and characteristics of homemade Asinan fruit products in running their business and can be used as an example. references by businesses engaged in food.